Analisis Kepuasan Pengguna Produk Laptop Asus Dikalangan Mahasiswa - Mustika Via Baharsah; Feoniy Amanda putri; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
This research aims to determine the effect of price and product quality on consumer loyalty through consumer satisfaction with Asus Laptop products. This research was conducted at Bina Bangsa University, with a sample size of one hundred and eighteen respondents where sampling used a survey method. From the results of the analysis, it was found that price had a positive influence on consumer loyalty. This can be positive because Asus laptops are one of the products most in demand by consumers, especially Asus laptops.